PENGARUH PEMBERIAN REWARD TERHADAP PERCAYA DIRI ANAK USIA 5-6 TAHUN DI RA PERWANIDA 4 PALEMBANG - Diah Ayu Nawang Wulan; Indah Wigati; Kurnia Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is entitled “The Effect of Rewards on the Self-Confidence of 5-6 Year Old Children at RA Perwanida 4 Palembang”. The problem addressed in this study is the low level of self-confidence among children. This study aims to determine whether rewards have an effect on the self-confidence of 5-6 year old children at RA Perwanida 4 Palembang. This study is a pre-experimental study with a one-group pre-test-post-test design. The sample in this study consisted of 15 children, comprising 7 boys and 8 girls. The data collection techniques used in this study were tests and documentation. The data analysis techniques used in this study were normality tests, homogeneity tests, and hypothesis tests. The hypothesis results were obtained after conducting the initial test (pre-test) and final test (post-test), then the researcher analyzed the research results. The results of data analysis in proving the hypothesis test obtained tcount = 93.8, while to determine ttable = 2.364 with a significance level of a = 0.05, the value of a/2 is 0.025, dk = n -1 = 15 – 1 = 14, so 0.02514 is obtained from ttabel 2.364. It can be concluded that tcount > ttabel, so Ha is accepted and Ho is rejected, which means that there is a significant effect of the reward method on the self-confidence of 5-6-year-old children at RA Perwanida 4 Palembang.